Association of Seawater Nanoparticle Size Distribution With Diversity of Marine Plankton - Jiang, Shuangcheng; Lin, Peimei; Cai, Yihua; Chen, Ding; Pan, Zhong; Lin, Hui; Wang, Fuli; Lin, Qi (Frontiers in Water, 2021)
Upon tangential ultrafiltration and asymmetric flow field analyses, seawater nanoparticle size distribution and the associations with the total number of bacteria and plankton diversity were evaluated. Of the nanoparticles in the Jiulong River Estuary, 79% were from 1 to 6 nm (C1). C2 (6–20 nm) was correlated with dissolved organic carbon, while C2 and C3 (>20 nm) were associated with dissolved inorganic nitrogen, suggesting that C2 and C3 were impacted by biogenic elements. The total number of bacteria was correlated with C1 and C3. The correlations of Shannon's diversity index (H′) and C3, richness (d), and C1 suggested a link of particle size with phytoplankton biodiversity. Significant correlations of the H′ of zooplankton and C3, and of Pielou's evenness index (J) and C3, suggested C3 as a primary digestion product of zooplankton. The negative correlations of nano-organic carbon (NOC) with d and J suggested NOC as a carbon source for zooplankton. Biodiversity was associated with seawater nanoparticle size distribution. Biological activities regulated the nanoparticle size distribution, which impacted the estuarine nutrient cycling, in turn affecting the stability and balance of biodiversity. Correlation analysis of the size distribution of seawater nanoparticles and the plankton diversity index provided a potential tool for evaluating ecological effects.